THE GEOGRAPHICAL PECULIARITIES OF TRANSFORMATION PROCESSES OF MECHANICAL ENGINEERING IN SUMY REGION - Корнус, Анатолій; Корнус, Олеся (Human Geography Journal, 2015)
The article is describes the mechanical engineering of Sumy region and its role in the industrial complex of the region. The current branch structure of engineering, the main centers and other network elements of mechanical engineering are analised. The dynamics of production mechanical engineering by product was highlights. Foreign economic relations of mechanical engineering field of the Sumy region are characterized. The transformation processes that have taken place in mechanical engineering of Sumy region during the 1991-2014 years were analyzed. The cartographic expression of these processes is given. The basic problems of the mechanical engineering sector and priority directions of its development are selected.